Toward practical issues: Identification and mitigation of the impurity effect in glyme solvents on the reversibility of Mg plating/stripping in Mg batteries - Yang, Zhenzhen; Yang, Mengxi; Hahn, Nathan T.; Connell, Justin; Bloom, Ira; Liao, Chen; Ingram, Brian J.; Trahey, Lynn (Frontiers in Chemistry, 2022)
Reversible electrochemical magnesium plating/stripping processes are important for the development of high energy density Mg batteries based on Mg anodes. Ether-glyme solutions such as monoglyme(G1), diglyme(G2) and triglyme(G3) with MgTFSI2 salt are one of the conventional and commonly used electrolytes that can obtain reversible behavior of Mg electrodes. However, the electrolyte cathodic efficiency is argued to be limited due to the enormous parasitic reductive decomposition and passivation, which is governed by impurities. In this work, a systematic identification of the impurities in these systems and their effect on the Mg deposition-dissolution processes are reported. The mitigation methods generally used for eliminating impurities are evaluated and their beneficial effects on the improved reactivity are also discussed. By comparing the performances, we propose a necessary conditioning protocol that can be easy to handle and much safer toward practical application of MgTFSI2/glyme electrolytes containing impurities.